Enhancement of self-compactability of fresh self-compacting concrete: A review - Bikila Meko (Elsevier, 2021)
The main characteristics of self-compating concrete (SCC) are its ability to flow into every corner of the formwork and even in congested reinforcement arrangements under its weight and without segregation. This paper reviews the recent progress in the enhancement of the self-compatibility of SCC in a fresh state. The main approaches to achieve this aim was observed to be the employment of air entrainment, and the utilization of various supplementary cementitious materials (SCMs) such as fly ash, silica fume, ground-granulated blast-furnace slag and rice husk ash. Entraining suitable air bubbles had the potential to enhance the self-compatibility of fresh concrete while also being very beneficial in reducing the cement content of the SCC. The workability and rheological properties of fresh SCC was observed to be enhanced by the utilization of SCMs. SCMs also possess the advantages of pozzolanic and filler effects which are not in play for entrained air. For future work, researchers can explore statistical and intelligent multi-objective optimisation techniques for getting the best amount of SCMs that will maximize the fresh properties whilst considering its deleterious effect on the hardened properties.